2020
DOI: 10.3846/jeelm.2020.11831
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionised (Electrolysed) Water on the Rat Embryo Development

Abstract: The aim of this study was to investigate the effects ionised water has on embryonic development using Wistar rat animal model. For that purpose, alkaline and acidic water was prepared with a domestic water ioniser. It was found that the concentrations of Cl–, SO42– ions increased in acidic water, while in alkaline water, Ca2+ concentration decreased and halogenated hydrocarbon concentrations exceeded permitted levels. The animals were given test alkaline and acidic water, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 40 publications
1
2
0
Order By: Relevance
“…The data that support the findings of this study are openly available at https://docs.google.com/document/d/1tk-kbOdGBW8SR-a0_1CNLnJMUtrXK7RJ/edit?usp=drivesdk&ouid=102821874409078598869&rtpof=true&sd=true, reference number 73.…”
Section: Data Availability Statementsupporting
confidence: 58%
See 1 more Smart Citation
“…The data that support the findings of this study are openly available at https://docs.google.com/document/d/1tk-kbOdGBW8SR-a0_1CNLnJMUtrXK7RJ/edit?usp=drivesdk&ouid=102821874409078598869&rtpof=true&sd=true, reference number 73.…”
Section: Data Availability Statementsupporting
confidence: 58%
“…Dibromoacetic acid and bromodichloromethane can pass through amniotic fluid, placentas, fetuses (rats and rabbits), or milk (rats) (Christian et al, 2001). Thus, these compounds have induced pregnancy loss (Narotsky et al, 2011), adverse pregnancy outcomes (APO) like short gestational age and stillbirth (Bonou, Levallois, Giguère, Rodriguez, & Bureau, 2017; Cao et al, 2016; Mashau, Ncube, & Voyi, 2018; Save‐Soderbergh, Toljander, Donat‐Vargas, Berglund, & Åkesson, 2020; Summerhayes et al, 2021), congenital central nervous system anomalies (Hwang & Jaakkola, 2003), skeletal defects (Stankevič et al, 2020), pre‐term delivery (King, Dodds, & Allen, 2000). Pregnant women who drank more than five glasses of water with DBP concentrations of about 75 μg/L each day displayed a significant relationship between APO and DBP and most exhibited intrauterine growth retardation (Wright, Schwartz, & Dockery, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, another study evaluated the effects of administering acidic (pH 3.4) or alkaline (pH 10.1) ionized water on embryonic development compared to neutral control water. It was revealed that both the acidic and alkaline groups resulted in a higher embryonic death, as well as impaired growth of the surviving fetuses [ 33 ].…”
Section: Safety and Concerns Of Erw Ingestionmentioning
confidence: 99%